Knowledge, Attitude, Actions on the Use of Personal Protective Equipment (PPE), and PPE Facilities and Infrastructure for Infectious Waste Management Workers at Siti Khodijah Hospital, Sepanjang, Sidoarjo - Hadi Suryono; Tsaabitah Hapsari; Demes Nurmayanti; Suprijandani; Winarko; Irwan Sulistio; Mahawiraja Setiawan (Gema Lingkungan Kesehatan, 2024)
A hospital for type B in Sidoarjo, in the section of infectious waste management, has already implemented the use of Personal Protective Equipment (PPE). However, the use of complete PPE is still lacking. As a result, there was a work accident in 2010 where a worker suffered from a skin infection caused by infectious waste. The aim of this study is to describe the knowledge, attitudes, actions on the use of PPE, and the facilities and infrastructure of PPE among infectious waste management workers at a type B hospital in Sidoarjo in 2023. This research is a descriptive observational study, with a sample population of 10 infectious waste management workers using a total sampling technique. The variables studied are the knowledge, attitudes, actions on the use of PPE, and the facilities and infrastructure of PPE among infectious waste management workers. Data analysis was performed univariately. The results showed that out of 10 people, 8 people (80%) had good knowledge and 2 people (20%) had sufficient knowledge. 7 people (70%) had good attitudes and 3 people (30%) had sufficient attitudes. 4 people (40%) had good actions and 6 people (60%) had sufficient actions. Additionally, 3 people (30%) had good PPE facilities and infrastructure and 7 people (70%) had sufficient PPE facilities and infrastructure. The conclusion obtained from this study is that the knowledge and attitudes of the workers are categorized as good, while the actions of the workers and the PPE facilities and infrastructure are categorized as sufficient. The suggestion is to pay more attention to the availability, completeness, and comfort of the PPE facilities and infrastructure needed by infectious waste management workers, and to conduct research on the use of PPE.